Respuestas

2012-10-29T03:08:25+01:00

Factor Comun 3x+3 = 3(x+1)

                     25x+12+3= 5(5x+3)

                     9+15-12+27= 3(3+5-4+9)

                      3a^3 – a^2 = a^2 (3a-1)

                      15c^3 d^2 + 60 c^2 d^3 = 15c^2 d^2 (c + 4d)

               

Trinomio: x^2+4x+4 = (x+2)(x+2)

                36x2+12xy2+y4  = (6x+y2)(6x+y2)

                4x^2 – 20xy – 25y^2 = (2x – 5y) (2x – 5y) 

                (5y – 2x)^2 = 25y^2 – 20xy + 4x^2

                x2 − 2x + 1 =(x-1)(x-1)

Suma por su Diferencia: x^2-9 = (x+3)(x-3)

                                    49x^2y^6z^0–a^12 =(7x y^3 z^5 + a^6 ) (7 x y^3 z^5 – a^6 )

                                    49x^2y^6z^10–a^12 = (7x y^3 z^5 + a^6 ) (7 x y^3 z^5 – a^6 )

                                      36a^2 – 64b^2 = (6a + 8 b) (6a – 8b)

                                     16m^2 – 100 = (4m + 10) (4m – 10)